Structure/function correlations over binuclear non-heme iron active sites - Solomon, Edward I. (J Biol Inorg Chem, 2016)
Binuclear non-heme iron enzymes activate O(2) to perform diverse chemistries. Three different structural mechanisms of O(2) binding to a coupled binuclear iron site have been identified utilizing variable-temperature, variable-field magnetic circular dichroism spectroscopy (VTVH MCD). For the μ-OH-bridged Fe(II)(2) site in hemerythrin, O(2) binds terminally to a five-coordinate Fe(II) center as hydroperoxide with the proton deriving from the μ-OH bridge and the second electron transferring through the resulting μ-oxo superexchange pathway from the second coordinatively saturated Fe(II) center in a proton-coupled electron transfer process. For carboxylate-only-bridged Fe(II)(2) sites, O(2) binding as a bridged peroxide requires both Fe(II) centers to be coordinatively unsaturated and has good frontier orbital overlap with the two orthogonal O(2) π* orbitals to form peroxo-bridged Fe(III)(2) intermediates. Alternatively, carboxylate-only-bridged Fe(II)(2) sites with only a single open coordination position on an Fe(II) enable the one-electron formation of Fe(III)–O(2)(−) or Fe(III)–NO(−) species. Finally, for the peroxo-bridged Fe(III)(2) intermediates, further activation is necessary for their reactivities in one-electron reduction and electrophilic aromatic substitution, and a strategy consistent with existing spectral data is discussed.